2022
DOI: 10.3390/ijms232113105
|View full text |Cite
|
Sign up to set email alerts
|

Development and Clinical Validation of RT-LAMP-Based Lateral-Flow Devices and Electrochemical Sensor for Detecting Multigene Targets in SARS-CoV-2

Abstract: Consistently emerging variants and the life-threatening consequences of SARS-CoV-2 have prompted worldwide concern about human health, necessitating rapid and accurate point-of-care diagnostics to limit the spread of COVID-19. Still, However, the availability of such diagnostics for COVID-19 remains a major rate-limiting factor in containing the outbreaks. Apart from the conventional reverse transcription polymerase chain reaction, loop-mediated isothermal amplification-based (LAMP) assays have emerged as rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The findings demonstrated that although the multigene approach enabled positive detection utilizing more target areas, the lateral flow dip strips produced false-negative results for two samples. The designed assays, such as the electrochemical sensor for N-gene and lateral flow device (LFD)-based RT-LAMP test, showed agreement with RT-PCR findings, suggesting their potential for a precise and sensitive diagnosis of COVID-19, particularly in the setting of developing variants with numerous mutations. …”
Section: Applicationmentioning
confidence: 76%
See 1 more Smart Citation
“…The findings demonstrated that although the multigene approach enabled positive detection utilizing more target areas, the lateral flow dip strips produced false-negative results for two samples. The designed assays, such as the electrochemical sensor for N-gene and lateral flow device (LFD)-based RT-LAMP test, showed agreement with RT-PCR findings, suggesting their potential for a precise and sensitive diagnosis of COVID-19, particularly in the setting of developing variants with numerous mutations. …”
Section: Applicationmentioning
confidence: 76%
“…The designed assays, such as the electrochemical sensor for N-gene and lateral flow device (LFD)-based RT-LAMP test, showed agreement with RT-PCR findings, suggesting their potential for a precise and sensitive diagnosis of COVID-19, particularly in the setting of developing variants with numerous mutations. 100 102 …”
Section: Applicationmentioning
confidence: 99%
“…This can be circumvented by visualising the amplification results under the illumination of UV light, which can be observed by the naked eye [ 18 ]. A slightly more sophisticated read-out method is the use of lateral flow-based strips for the detection of amplified SARS-CoV-2 viral mRNA [ 19 , 20 ]. A further simplification could be sought by using less sophisticated (or even non) nucleic acid extraction methods [ 21 ], but these will need further validation, particularly for RNA.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a RT-LAMP assay, combined with electrochemical biosensors, has been employed for the diagnosis of COVID-19 (SULEMAN, et al 2021;KUMAR et al, 2022b). Briefly, this technology consists of adding amplicons from RT-LAMP to the biosensor surface with the aim of improving the detection of virus target sequences through hybridization with specific probes (SAXENA et al 2022). Additionally, RT-LAMP, combined with CRISPR/Cas, has been employed to improve the sensitivity and specificity of SARS-COV-2 detection (SELVAM et al, 2021;REZAEI et al, 2021;BHATT et al 2022).…”
Section: Rt-lamp: Reverse Transcription Lampmentioning
confidence: 99%